Implementasi Peraturan Pemerintah Nomor 58 Tahun 2023 terhadap Pajak Penghasilan Pasal 21 bagi Wajib Pajak Orang Pribadi - Vivianti Indar Yusnia; Dian Fahriani (Fakultas Ekonomi Universitas 45 Surabaya, 2026)
This study aims to analyze the application of Government Regulation Number 58 of 2023 in the calculation of Article 21 Income Tax for individual taxpayers on the income received. The approach used in this study is qualitative, with a descriptive qualitative research type. The research data consists of secondary data in the form of tax reports implementing the Tax Effective Rate (TER), as well as primary data obtained through observations and interviews with individual taxpayers whose income has been subject to Article 21 Income Tax withholding using TER. The results of the study indicate that the salary and fixed allowances received by Mr. R are subject to Article 21 Income Tax withholding with varying amounts in each tax period. In the December period, the amount of tax underpayment is relatively smaller because it has considered the accumulation of Article 21 Income Tax withholding from January to November. Thus, the implementation of Government Regulation Number 58 of 2023 has a positive impact, marked by significant tax cuts during the current period but resulting in lower tax liabilities at the end of December.